Türk vergi sisteminde belge düzeni - Somuncu, Ahmet (My University, 2005)
TÜRK VERGİ SİSTEMİNDE BELGE DÜZENİ Bu doktora tezinde “Türk Vergi Sisteminde Belge Düzeni” incelenmiştir. Türk vergi sisteminin dayandığı beyan ilkesinin bir gereği olarak, vergi yükümlülerine bazı şekli ödevleri yüklenmiştir. Bunlardan birisi de belge düzenine uymaktır. Buna ilişkin hükümler Vergi Usul Kanunu'nun ikinci kitabında; Vesikalar başlığı altında düzenlenmiştir. Ayrıca Maliye Bakanlığı’nın belge düzenine ilişkin düzenleme yapma yetkisi bulunmaktadır. Belge Düzenine Uyma Ödevi mali hukuk literatüründe genel bir kabul görmüş bir kavramdır. Bu ödeve ilişkin belgeler, vergiyi doğuran ekonomik olayların kayıt altına alınmasını ve vergi matrahının belirlenmesini sağlayan belgelerdir. Öte yandan belge düzeni; muhasebe kayıtlarına esas teşkil eder ve muhasebe hukukunun “belgesiz kayıt olmaz” temel prensibinin gerçekleşmesini sağlar. Ticaret Hukuku bakımından ise; fatura önemli bir ispat aracı olarak karşımıza çıkmaktadır. Belge düzeni; belgelerin verilmesi, alınması, saklanması ve istendiğinde ibrazı zorunluluğu getirmektedir. Ayrıca belgelerin yasal şekil şartlarına uyulması konularını içermektedir. Belge düzenine uyulmaması halinde parasal ve hürriyeti bağlayıcı cezalar öngörülmüştür. Bu çalışmada belge düzeni içerisinde yer alan belgeler, vergi, muhasebe ve ticaret hukuku bakımından ele alınmıştır. Son yıllarda belgelere ilişkin vergi mevzuatı oldukça karmaşık bir hal almış, bu da vergi mükelleflerine külfet getirmiştir. Özellikle Maliye Bakanlığı’nın bu konuda yaptığı düzenlemelerin bu karmaşıklığın önemli sebeplerinden biri olduğu bu çalışmanın sonuçları arasında yer almaktadır. Name and Surname: Ahmet Somuncu Field: Finance Programme: Fiscal Law Supervisor: Professor Ömer Faruk Batırel Degree Awarded and Date: Doctorate- July 2005 Document Regime, Documentary Evidence, Obligations of Taxpayers, Turkish Tax System, Tax Procedure Code

DOCUMENT REGIME IN TURKISH TAX SYSTEM In this PhD Thesis “Document Regime in Turkish Taxation System” is investigated. Due to the fact that Turkish taxation system depends on declaration principle, tax liabilities are obliged to obey certain formats of norm duties. One of them is to comply with the document regime. These are regulated under the heading of “Documents” in the second volume of Tax Procedure Code. Besides, Ministry of Finance is authorized to regulate documentation regime. “Duty of Compliance with the Document Regime” is a generally accepted concept in the fiscal law literature. Documents of this duty are the records of the tax generating economic activities and the documents that maintain the basis of tax assessments. Documentation regime is the basis of accountancy transactions and maintains the realization of “No document- No accounting” basic principle. Commercial Code accepts the invoice as a document of verification. Documentation regime brings obligation of giving, taking, keeping and submission of the documents. Also includes the obligations to comply with the legal formats of norm of the documents. In case of incompliance to the documentation regime stipulations of pecuniary fines or imprisonment are predicted. In this study documents included in the regime are investigated from taxation, accounting and commercial codes point of views. In the recent years subjects under current laws become very complicated implementing the tax liabilities into tedious and complicated works. As a conclusion of this study, regulations made by the Ministry of Finance are observed to be one of the main reasons in these complications.
Keywords: Vergiler_Türkiye